Engineered cell culture microenvironments for mechanobiology studies of brain neural cells - Castillo Ransanz, Lucía; Van Altena, Pieter F. J.; Heine, Vivi M.; Accardo, Angelo (Frontiers in Bioengineering and Biotechnology, 2022)
The biomechanical properties of the brain microenvironment, which is composed of different neural cell types, the extracellular matrix, and blood vessels, are critical for normal brain development and neural functioning. Stiffness, viscoelasticity and spatial organization of brain tissue modulate proliferation, migration, differentiation, and cell function. However, the mechanical aspects of the neural microenvironment are largely ignored in current cell culture systems. Considering the high promises of human induced pluripotent stem cell- (iPSC-) based models for disease modelling and new treatment development, and in light of the physiological relevance of neuromechanobiological features, applications of in vitro engineered neuronal microenvironments should be explored thoroughly to develop more representative in vitro brain models. In this context, recently developed biomaterials in combination with micro- and nanofabrication techniques 1) allow investigating how mechanical properties affect neural cell development and functioning; 2) enable optimal cell microenvironment engineering strategies to advance neural cell models; and 3) provide a quantitative tool to assess changes in the neuromechanobiological properties of the brain microenvironment induced by pathology. In this review, we discuss the biological and engineering aspects involved in studying neuromechanobiology within scaffold-free and scaffold-based 2D and 3D iPSC-based brain models and other approaches employing primary lineages (neural/glial), cell lines and pluripotent stem cells. Finally, we discuss future experimental directions of engineered microenvironments in neuroscience.